Hubungan Pengetahuan Ibu Hamil Tentang HIV-AIDS dengan Pemanfaatan Pemeriksaan HIV oleh Ibu Hamil di Puskesmas Bintang Kabupaten Aceh Tengah Tahun 2022 - Elika Fitri; Nur Azizah; Rosmani Sinaga; Sri Wahyu Nduru; Kamelia Sinaga (NAJ Nursing Applied Journal, 2025)
HIV/AIDS is an infectious disease that has a serious impact on the immune system and is at high risk in pregnant women. Mother-to-baby transmission of HIV can occur during pregnancy, childbirth, and breastfeeding. HIV screening in pregnant women is important for the prevention of vertical transmission. However, the utilization rate of this test is still low, one of which is due to the lack of knowledge of pregnant women about HIV/AIDS. This study aims to determine the relationship between pregnant women's knowledge about HIV and the use of HIV testing at the Bintang Health Center, Central Aceh Regency in 2022. This study uses an analytical observational design with a cross sectional approach. The research sample amounted to 40 pregnant women who were selected by purposive sampling. Data was collected through questionnaires and analyzed using the Chi-Square test. The results showed that the majority of pregnant women had sufficient knowledge about HIV/AIDS (40%) and most did not do HIV screening (55%). There was a significant relationship between pregnant women's knowledge about HIV and the use of HIV screening (p-value = 0.0001). There is a significant relationship between pregnant women's knowledge about HIV-AIDS and the use of HIV screening by pregnant women at the Bintang Health Center, Central Aceh Regency. Intervention efforts in the form of education and counseling are needed to increase the knowledge of pregnant women to encourage routine HIV testing in an effort to prevent HIV transmission from mother to child.